Peranan Mediator Dalam Memediasi Perkara Waris di Pengadilan Agama Medan - Warohmah, Mawaddah (Jurnal Landraad, 2022)
The Religious Court has implemented mediation in accordance with Supreme Court Regulation No. 1 of 2016. However, in reality, there exists a gap between theory and implementation, particularly in inheritance cases at the Medan Religious Court. This research aims to discuss the process undertaken by mediators in resolving inheritance disputes at the Medan Religious Court and assess the effectiveness achieved by the mediators in settling inheritance disputes. The research adopts a qualitative approach with a socio-legal perspective, examining the legal aspects of the social phenomenon. Data sources were obtained through literature reviews supported by interviews with the mediators and lawyers who have handled inheritance cases at the Medan Religious Court. The findings of this research indicate that the mediation process conducted by mediators in resolving inheritance disputes at the Medan Religious Court consists of three stages: pre-mediation, mediation process, and mediation results. The steps taken in mediating inheritance disputes by the mediators at the Medan Religious Court align with and adhere to Supreme Court Regulation No. 1 of 2016. The process of settling inheritance disputes through mediation by the mediators at the Medan Religious Court can proceed smoothly and efficiently, concluding with a peaceful agreement between the conflicting parties.